Immune Pathobiology of Schwannomas: A Concise Review - Elmaci, İlhan; Altinoz, Meric A.; Sari, Ramazan (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2018)
Schwannomas are benign tumors treatable with neurosurgery or radiosurgery, yet a small subset may exhibit aggressive growth. Hence illuminating their immune features can help develop better treatments. A tumor-promoting inflammation exists in schwannomas. Transcription factor NF-κB triggers synthesis of inflammatory cytokines and chemokines. NF-κB is suppressed by NF2/merlin, yet it is mutated or repressed in schwannomas, and therefore MCP-1/CCL2, MIP-1α/CCL3, CXCL16, and CXCR6/Bonzo are likely expressed in these tumors. CD68+ and CD163+ macrophages may infiltrate schwannomas and promote their growth. Anti-inflammatory salicylates inhibit schwannomas in cell culture and clinically. Schwannomas that cannot be completely removed by neurosurgery or controlled by radiosurgery may be suitable targets of pharmacologic interventions focusing on immune mechanisms.
Keywords: schwannoma; merlin; immunity; NF-κB; macrophage